Penentuan Aktivitas Biologis Tanin Beberapa Hijauan secara in Vitro Menggunakan ’Hohenheim Gas Test’ dengan Polietilen Glikol Sebagai Determinan - A Jayanegara; A Sofyan (Media Peternakan, 2008)
Leaves from trees are alternative source of forage for ruminant's feed. However, most of the leaves contain high concentration of phenolic compounds, especially in the form of tannins. This experiment was aimed at quantifying biological activity of tannins using in vitro gas production method without and with the addition of polyethylene glycol (PEG). The leaves used in this experiment was Salix alba, Rhus typhina and Peltiphyllum peltatum. Several rumen fermentation variables, such as organic matter digestibility (OMD), metabolizable energy (ME) and total VFA production were measured. The results showed that crude protein, NDF and hemicellulose contents of S. alba leaves were the highest, while there was no difference in ADF content from the others. Biological activity of tannins in S. alba, R. Typhina and P. Peltatum were 0.7%, 45.7% and 122.6%, respectively. There was a significant correlation between total phenols and tannins biological activity (r=0.70; P < 0.05), whereas no significant correlation was found for total tannins and condensed tannins. It was concluded that the addition of PEG increased in vitro gas production, organic matter digestibility, metabolizable energy and total VFA production after 24 hours incubation period. Key words: tannins, PEG, in vitro, fermentation, Hohenheim gas test